(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2026)
Translation is a key factor in determining the global reach and popularity of science fiction literature. By transferring narratives across languages and cultures, translators enable readers to engage with imaginative worlds, speculative technologies, and culturally embedded ideas. This article investigates the strategies and methods translators use to preserve meaning, style, and cultural relevance while making science fiction accessible. Drawing on examples from prominent science fiction works, the study highlights how translation decisions affect readership, comprehension, and international reception. The findings demonstrate that translation is an interpretive and creative process that shapes both the literary experience and the global popularity of science fiction.